Risk assessment of thromboembolic events in hospitalized cancer patients - Nichetti, Federico; Ligorio, Francesca; Montelatici, Giulia; Porcu, Luca; Zattarin, Emma; Provenzano, Leonardo; Franza, Andrea; Lalli, Luca; de Braud, Filippo; Platania, Marco (Scientific reports, 2021)
Hospitalized cancer patients are at increased risk for Thromboembolic Events (TEs). As untailored thromboprophylaxis is associated with hemorrhagic complications, the definition of a risk-assessment model (RAM) in this population is needed. INDICATE was a prospective observational study enrolling hospitalized cancer patients, with the primary objective of assessing the Negative Predictive Value (NPV) for TEs during hospitalization and within 45 days from discharge of low-grade Khorana Score (KS = 0). Secondary objectives were to assess KS Positive Predictive Value (PPV), the impact of TEs on survival and the development of a new RAM. Assuming 7% of TEs in KS = 0 patients as unsatisfactory percentage and 3% of as satisfactory, 149 patients were needed to detect the favorable NPV with one-sided α = 0.10 and power = 0.80. Stepwise logistic regression was adopted to identify variables included in a new RAM. Among 535 enrolled patients, 153 (28.6%) had a KS = 0. The primary study objective was met: 29 (5.4%) TEs were diagnosed, with 7 (4.6%) cases in the KS = 0 group (NPV = 95.4%, 95% CI 90.8-98.1%; one-sided p = 0.084). However, the PPV was low (5.7%, 95% CI 1.9-12.8%); a new RAM based on albumin (OR 0.34, p = 0.003), log(LDH) (OR 1.89, p = 0.023) and presence of vascular compression (OR 5.32, p < 0.001) was developed and internally validated. Also, TEs were associated with poorer OS (median, 5.7 vs 24.8 months, p < 0.001). INDICATE showed that the KS has a good NPV but poor PPV for TEs in hospitalized cancer patients. A new RAM was developed, and deserves further assessment in external cohorts.
Gesehen am 11.11.2021